DEIXIS IN THE SHORT STORY AL-ISTIGHOTSAH BY ZAKARIA TAMER: A PRAGMATIC ANALYSIS: DEIKSIS PADA CERPEN AL-ISTIGHOTSAH KARYA ZAKARIA TAMER: KAJIAN PRAGMATIK - Sukmono, Hilmy Aqila; Al Anshory, Abdul Muntaqim (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Deixis plays a crucial role in literary discourse by linking language to its narrative and social context. Despite its significance, pragmatic studies on deixis in Arabic literary texts remain limited. This study aims to analyze the use of deixis in the Arabic short story Al-Istighāthah by Zakaria Tamer using Yule’s (1996) theory. The research focuses on identifying and interpreting three types of deixis—personal, temporal, and spatial—and how they function within the narrative. Employing a descriptive qualitative method with contextual analysis, the data were derived from selected excerpts of the short story. The findings reveal that personal deixis clarifies character roles and relationships through pronoun usage, temporal deixis constructs the chronological framework via expressions such as al-ān and past-tense verbs, while spatial deixis situates events using references like bi-al-qurbi minhumā and fawqa arḍi Maysalūn. These deixis types do not merely serve referential functions but also reflect the emotional, social, and historical dimensions of the text. This study contributes to the pragmatic-stylistic analysis of Arabic literary works by highlighting how deixis shapes meaning and narrative engagement within a culturally loaded context.